Odpowiedź :
a)
x²-2x+1-(y²-6y+9)=x²+xy-xy-y²
x²-2x+1-y²+6y-9=x²+xy-xy-y²
x²-2x-y²+6y-x²-xy+xy+y²=9-1
-2x+6y=8
b)
x+2-y+⁴/₃=1
x-y=1-⁴/₃ -2
x-y= ³/₃ - ⁴/₃ - ⁶/₃
x-y= - ¹³/₃
x-y= -4 ¹/₃
x²-2x+1-(y²-6y+9)=x²+xy-xy-y²
x²-2x+1-y²+6y-9=x²+xy-xy-y²
x²-2x-y²+6y-x²-xy+xy+y²=9-1
-2x+6y=8
b)
x+2-y+⁴/₃=1
x-y=1-⁴/₃ -2
x-y= ³/₃ - ⁴/₃ - ⁶/₃
x-y= - ¹³/₃
x-y= -4 ¹/₃
(x-1)² - (y-3)² = (x-y) (x+y)
x+4/₂ - y+4/₃ = 1
x²-2x+1-(y²-6y+9)=x²-y²
x+2-y+4/3=1
x²-2x+1-y²+6y-9=x²-y²
x-y=1- 10/3
x²-2x-y²+6y-x²+y²=8
x-y=-7/3
-2x+6y=8
x=y-7/3
-2(y-7/3)+6y=8
x=y-7/3
-2y+14/3+6y=8
x=y-7/3
4y=8-14/3
x=y-7/3
4y=10/3
x=y-7/3
y=5/6
x=5/6-7/3
y=5/6
x=5/6-14/6
y=5/6
x=-9/6
y=5/6
x=-3/2
x+4/₂ - y+4/₃ = 1
x²-2x+1-(y²-6y+9)=x²-y²
x+2-y+4/3=1
x²-2x+1-y²+6y-9=x²-y²
x-y=1- 10/3
x²-2x-y²+6y-x²+y²=8
x-y=-7/3
-2x+6y=8
x=y-7/3
-2(y-7/3)+6y=8
x=y-7/3
-2y+14/3+6y=8
x=y-7/3
4y=8-14/3
x=y-7/3
4y=10/3
x=y-7/3
y=5/6
x=5/6-7/3
y=5/6
x=5/6-14/6
y=5/6
x=-9/6
y=5/6
x=-3/2